Aile Hekimliği Polikliniğine Başvuran 35 Yaş ve Üzeri Hastaların Kanser Tarama Testleri Hakkında Bilgi ve Tutumları. - ÖZSÖYLER, Muazzez; ÇAPAR, Zeliha GÜZELÖZ; KESER, Murat (Forbes Journal of Medicine, 2023)
Objective: The treatment of cases diagnosed at the early stage is easier and less costly than advanced stage cases, and the effect on the quality of life of patients is great. In this study, we evaluated the level of knowledge and attitude of patients about cancer screening and, as a result, to increase their awareness. Methods: The study included 230 people over 35 years of age who applied to University of Health Sciences Turkey, İzmir Tepecik Training and Research Hospital Family Physician outpatient clinics between December 2017 and January 2018. Participants used a face-to-face interview questionnaire consisting of 32 questions. Our study was descriptive. The Statistical Package for the Social Sciences 20.0 program was used in the analysis of the data. Results: The average age of the participants, 54% were female, 87% were married, 37.8% were primary school graduates, 68.7% were middle income, and the age of 45-54 is the most common group. 72.2% of the participants stated that they had information about cancer screenings. 6.1% of those participating in the study stated that they regularly had cancer screening. 31.8% of womans had smear test. 50.8% of womans stated that they did the manual breast examination. 10.0% had fecal ocult blood testand 4.3% had colonoscopy. Conclusion: In our study, we found that most of the participants were missing information about cancer screening tests, and we have found that the rate of consignment is low. Risk groups should be informed of more about cancer screening and encouraged to do screening tests. Training should be organized in this regard.